2018
DOI: 10.1155/2018/6789076
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Functionalized Carboxymethyl-β-Cyclodextrin: Synthesis, Characterization, and Photostability

Abstract: e resveratrol functionalized carboxymethyl-β-cyclodextrin conjugate was synthesized by two simple steps. e conjugate was successfully demonstrated by 1 H NMR, 13 C NMR, UV, and FTIR. e photostability of the conjugate was studied by ultraviolet absorption spectrum. After 360 min of UV light irradiation, the conjugate showed a total loss in absorbance of only 12.54%, while the resveratrol and its CM-β-CD inclusion complex showed a total loss in absorbance of 32.15% and 24.05%, respectively. e results indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
(36 reference statements)
1
10
0
Order By: Relevance
“…Cheng et al . successfully modified resveratrol with cyclodextrin and explored the photo‐stability of the derivative; the results showed that the method could enhance the photo‐stability of resveratrol . When resveratrol formed inclusion complexes with different cyclodextrin, its stability was enhanced .…”
Section: Stabilitymentioning
confidence: 99%
“…Cheng et al . successfully modified resveratrol with cyclodextrin and explored the photo‐stability of the derivative; the results showed that the method could enhance the photo‐stability of resveratrol . When resveratrol formed inclusion complexes with different cyclodextrin, its stability was enhanced .…”
Section: Stabilitymentioning
confidence: 99%
“…The complex formation between resveratrol and sulfobutylether-β-CD significantly increased the water solubility of resveratrol while loading them into polymeric nanoparticles [ 78 ]. The resveratrol solubility improved due to its complexation with permethylated β-CD, 2,6-dimethylated β-CD and permethylated α-CD [ 79 ] and the photostability was achieved because of its complexation with carboxymethyl-β-CD [ 80 ]. By using a cyclodextrin glucanotransferase enzyme, resveratrol α-glycosides were synthesized directly from β-CD-resveratrol complexes in water.…”
Section: Bioavailability Of Resveratrolmentioning
confidence: 99%
“…The complex formation between resveratrol and sulfobutylether-β-CD significantly increased the water solubility of resveratrol while loading them into polymeric nanoparticles [78]. The resveratrol solubility improved due to its complexation with permethylated β-CD, 2,6-dimethylated β-CD and permethylated α-CD [79] and the photostability was achieved because of its complexation with carboxymethylβ-CD [80]. By using cyclodextrin glucanotransferase enzyme, resveratrol α-glycosides were synthesized directly from β-CD-resveratrol complexes in water.…”
Section: Application Of Cyclodextrins In Resveratrol Deliverymentioning
confidence: 99%